The Roles of Dental Professionals Team among the Family Care Team Policy in Lower-Northern Region, Thailand - Sangouam, Supaporn (UI Scholars Hub, 2018)
Objective: To determine the roles of dental personnel in the Family Care Team Policy in Lower–Northern region, Thailand. Methods: Purposively selected samples were collected from 15 dental personnel in the lower Northern region, Thailand, an in-depth, semistructured interview was conducted, and data were analyzed thematically. Results: The main roles of the dental professional team according to the Family Care Team Policy consisted of a continuous care role in the patient’s home, primary dental health services, risk screening and provision of services as needed, and health promotion and oral disease prevention. The most challenging role of the multidisciplinary dental professional team was the continuous care role at home. The dentist has a role as a complex case counselor, while the role of dental hygienist is in coordinating and supporting patient information provided to the dentist. The multidisciplinary team provides basic knowledge to caregivers regarding patient’s oral hygiene and dental care consult, and/or refers patients to the dentist in complex cases. Conclusion: The important role of the dental professional team is to support and join the Family Care Team to provide effective holistic care to patients, especially dependent elderly, disabled, and end-of-life patients, thus, constituting a multidisciplinary team which is the most challenging role of dental professionals.